AZD8055 Is More Effective Than Rapamycin in Inhibiting Proliferation and Promoting Mitochondrial Clearance in Erythroid Differentiation - Qian Liu; Tao Hao; Ze Lin; Yipeng Fang; Lei Li; Daqi Huang; Jianbo Wu; Yanchao Zhao; Xin Zhang (Analytical Cellular Pathology)
Conclusion: AZD8055 is more effective than rapamycin in inhibiting proliferation and promoting mitochondrial clearance in erythroid differentiation, which might provide us one more therapeutic option other than rapamycin for ineffective erythropoiesis treatment in the future. These findings also provide some preliminary information indicating the roles of mTORC1 and mTORC2 in erythropoiesis, and further studies are necessary to dissect the underlying mechanisms.